2023
DOI: 10.1177/17449871231182837
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between workplace violence, emotional exhaustion, job satisfaction and turnover intention among nurses during the COVID-19 pandemic

Abstract: Objectives: Workplace violence is a major issue in society, business and healthcare settings. It adversely affects both employee safety and their ability to provide healthcare services. Aim: This study examined the association between workplace violence, emotional exhaustion, job satisfaction and turnover intention among nurses during the COVID-19 pandemic. Methods: We collected data from 513 nurses. We conducted ‘Process Macro’ analysis. Firstly, we included three mediators in the model: job satisfaction, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Verbal and psychological violence also has serious effects on nursing students who complain about high job strain, low social support, and low organizational justice [76] that produce a negative effect on their professional commitment [77]. Workplace violence in HCWs may be associated with burnout and the intention to quit [78], although this relationship can be mediated by work ability [79].…”
Section: Discussionmentioning
confidence: 99%
“…Verbal and psychological violence also has serious effects on nursing students who complain about high job strain, low social support, and low organizational justice [76] that produce a negative effect on their professional commitment [77]. Workplace violence in HCWs may be associated with burnout and the intention to quit [78], although this relationship can be mediated by work ability [79].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the same study indicated that workplace violence and job satisfaction mediate the relationship between burnout and the intention to leave the job (Gedik et al, 2023). This study was conducted to determine how workplace violence experienced by health sector workers affects their job satisfaction and intention to leave, and whether work-family conflict plays a mediating role in this interaction.…”
Section: Job Satisfaction With Exposure To Violence Work-family Confl...mentioning
confidence: 99%
“…In another study, it was observed that workplace violence experienced by healthcare workers affects job satisfaction, the intention to leave the job, and burnout. Additionally, the same study indicated that workplace violence and job satisfaction mediate the relationship between burnout and the intention to leave the job ( Gedik et al, 2023 ).…”
Section: Introductionmentioning
confidence: 98%
“…As a result, these research methods were unable to fully reflect the trajectory of changes in emotional exhaustion in clinical nurses (Ding & Wu, 2023;Karaca et al, 2023;Zhang et al, 2023), and overlook the dynamic temporal variations in emotional exhaustion experienced by nursing staff over time. Besides, previous studies on the changes in emotional exhaustion often treated the psychological states of nurses as uniformly distributed, overlooking the issue of individual differences (Gedik et al, 2023;Rink et al, 2023). There was a lack of longitudinal exploration regarding the differential impact factors among different developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%